British Cardiovascular Interventional Society Consensus Position Statement on Out-of-Hospital Cardiac Arrest 1: Pathway of Care - Nilesh Pareek; Paul Rees; Tom Quinn; Johannes Von Vopelius-Feldt; Sean Gallagher; Abdul Mozid; Tom Johnson; Ellie Gudde; Rupert Simpson; Guy Glover; John Davies; Nick Curzen; et al. (Interventional Cardiology: Reviews, Research, Resources, 2022)
Out-of-hospital cardiac arrest (OHCA) affects 80,000 patients per year in the UK; despite improvements in care, survival to discharge remains lower than 10%. NHS England and several societies recommend all resuscitated OHCA patients be directly transferred to a cardiac arrest centre (CAC). However, evidence is limited that all patients benefit from transfer to a CAC, and there are significant organisational, logistic and financial implications associated with such change in policies. Furthermore, there is significant variability in interventional cardiovascular practices for OHCA. Accordingly, the British Cardiovascular Interventional Society established a multidisciplinary group to address variability in practice and provide recommendations for the development of cardiac networks. In this position statement, we recommend: the formal establishment of dedicated CACs; a pathway of conveyance to CACs; and interventional practice to standardise our approach. Further research is needed to understand the role of CACs and which interventions benefit patients with OHCA to support wide-scale changes in networks of care across the UK.